Selective utilization of fructose to glucose by Candida magnoliae, an erythritol producer - Yu, Ji-Hee; Lee, Dae-Hee; Oh, Yong-Joo; Han, Ki-Cheol; Ryu, Yeon-Woo; Seo, Jin-Ho (HUMANA PRESS INC, 2006)
Candida magnoliae isolated from honeycomb is an industrially important yeast with high erythritol-producing ability. Erythritol has been used as functional sugar substitute for various foods. In order to analyze the physiological properties of C. magnoliae, a study on sugar utilization pattern was carried out. The fermentation kinetics of glucose and fructose revealed that C. magnoliae has the discrepancy in glucose and fructose utilization when it produces erythritol. In contrast to most yeasts, C. magnoliae showed preference for fructose to glucose as a carbon source, deserving the designation of fructophilic yeast. Such a peculiar pattern of sugar utilization in C. magnoliae seems to be related to the evolutionary environment.